2007
DOI: 10.1093/her/cym055
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and environmental factors associated with cycling for transport among a working population

Abstract: The aim of this study was to examine psychosocial and environmental predictors of cycling for transportation. A sample of 343 Flemish adults (43% men) living at maximum 10 km from their workplace was surveyed. Self-report measures of cycling, demographic variables, psychosocial variables, self-efficacy, perceived benefits and barriers and environmental attributes (destination, traffic variables and facilities at the workplace) of cycling for transport were obtained by means of a mailing questionnaire. Modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
155
4
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 33 publications
20
155
4
11
Order By: Relevance
“…Additionally, middle-aged adults (aged 30 to 39.9 years) reported a higher frequency of bicycling for transportation, which is corroborated by other studies 7,9,12,13 . One hypothesis is that middle-aged adults are more economically active, and bicycles are an efficient and inexpensive way of arriving at work 14,19 ; however, the lack of information about travel destination prevents the testing of this hypothesis. The proportion of cyclists was higher among those with lower socioeconomic status, which is consistent with the literature 7,12,13,21 and supports the hypotheses presented above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, middle-aged adults (aged 30 to 39.9 years) reported a higher frequency of bicycling for transportation, which is corroborated by other studies 7,9,12,13 . One hypothesis is that middle-aged adults are more economically active, and bicycles are an efficient and inexpensive way of arriving at work 14,19 ; however, the lack of information about travel destination prevents the testing of this hypothesis. The proportion of cyclists was higher among those with lower socioeconomic status, which is consistent with the literature 7,12,13,21 and supports the hypotheses presented above.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, the use of the bicycle for transportation and leisure is low, both in highincome countries 7,8 and in low-and middleincome countries 9,10 . In Brazil, an estimated 8 to 16% of adults commute by bicycle 11 , a prevalence similar to that of Canada 7,12,13 and Australia 8 but lower than in European countries 14,15,16 . The use of the bicycle in leisure time is one of the five most common forms of physical activity among Brazilian adults 17 .…”
Section: Introductionmentioning
confidence: 92%
“…Too dangerous, lack of sufficient fitness, lack of motivation, lack of facilities at work (showers, bike racks, etc. ), no bike lanes, personal safety during journey, bad weather, lack of proper lighting, distance, topography, lack of safe parking at destination, lack of cycling knowledge or experience, too much traffic, uncomfortable, difficulties with trip chaining, need to carry things, air pollution, free car parking at work, lack of time, and bad road conditions (3,4,6,9,16,(18)(19)(20)(21)(22).…”
Section: Cycling Habits and Other Psychological Variables Affecting Cmentioning
confidence: 99%
“…Using predetermined criteria, each segment of the network is given an LTS rating from 1 to 4, resulting in a map that shows which The value of such infrastructure for increasing cycling is mixed. While many studies have found a positive correlation between levels of bicycle infrastructure and bicycle commuting [15][16][17] others have found little correlation [18][19][20][21]. What is certain is that many cyclists prefer routes with bicycle facilities [22][23][24][25][26][27][28] and bicycle infrastructure encourages non-cyclists to try cycling [14].…”
Section: Audit Instruments For Bicycle Networkmentioning
confidence: 99%